Czlowiek z samotnych wysp - Roszel, Renee; Fabianowska, Malgorzata (Warszawa : Wydawnictwo Harlequin Enterprises, 1993)
Polish translation of "Bride for Ransom". A romantic story of two sisters who meet a mysterious man, Ransom Shepherd.
On cover: "grudzien '93"